TICK-BORNE PATHOGENS DETECTION FROM TICKS INFESTING Malayopython reticulatus (REPTILIA: PYTHONIDAE) SNAKES IN INDONESIA - Supriyono; Hana Faizah Sophia; Upik Kesumawati Hadi; Susi Soviana (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights: - A total of 38 ticks were collected from M. reticulatus, comprising 13 A. helvolum and 25 A. varanense. - Spotted fever group Rickettsia spp. (7.89%) and reptile-associated Borrelia sp. (2.63%) were detected in male Amblyomma helvolum ticks collected from Malayopython reticulatus snakes in Indonesia. - Snake-associated ticks may harbor emerging pathogens, underscoring the importance of tick surveillance in reptiles for early disease detection and zoonotic prevention.